Theme, transitivity and cognitive representation in spanish and english written texts - McCabe, Anne M.; Alonso Belmonte, Mª Isabel (Círculo de Lingüística Aplicada a la Comunicación, 2023)
Our aim in this paper is to explore the notion of Theme from a cognitive perspective. We see the pressures which are brought to bear on Theme choice as manifold, as these pressures come in varying degrees from the three metafunctions: the interpersonal, the textual, and the experiential. It is this last component, with respect to the text producer’s cognitive perspective of reality, which is focused on here. To this end, using a discoursal cognitive perspective, we expand the functional conception of Theme, and review other analysts’ (Ghadessy, 1993; Fries, 1995a; inter alia) results on Theme selection, as well as provide results from our own contrastive studies on Theme in Spanish and English. We conclude that, since Theme choice is linked to the contextual configuration of the text, the way in which text producers view the field of discourse, i.e. their cognitive representation of the field, is a contributing factor in motivation for Theme selection.